Dexmedetomidine versus Lidocaineversus Ketamine to Alleviate Propofol Injection Pain: A Prospective Randomized Double Blind Study - Ranjini BN; Vijay Siddhartha B S (Academia Anesthesiologica International, 2020)
Background: Ketamine (a phencyclidine derivative) has been recognized as a potent analgesic and local anesthetic properties but few studies have also been conducted to evaluate the utility of ketamine in reducing propofolinjection pain. Exact mechanism of analgesia effect is not clear. Subjects and Methods: 50 adult patients, in each group [group D, group L and group K] satisfying the inclusion criteria. The sample size is calculated based on previous studies as well as approximate availability of number of cases in the above mentioned duration satisfying inclusion and exclusion criteria in our college. Size of patients in each group is arrived at with 90% power at an alpha value of 0.05 to detect a 25% difference in severity of pain between the three groups. Results: There was a statistically significant difference in MAP and HR between the study groups. This may be attributed to the activation of the sympathetic nervous system by ketamine. Conclusion: As a consequence , BP is increased, which may attenuate the hypotensive effect of the propofol injection in our study.